Impacto del COVID-19 en el ámbito socioeconómico del pasaje comercial San Cayetano en el cantón Chone - Solórzano Solórzano, Pedro Querubín (2023)
The impact of COVID-19 on the socioeconomic environment of the San Cayetano Commercial Passage in Chone canton has been significant. Through the evaluation of the current situation, several indicators have been identified that show the impact of the pandemic in this area of study. One of the main problems found is the lack of control to detect people infected by COVID-19. This has led to an increase in infections and the risk of outbreaks and closures of operations. Another problem identified is the lack of training plans for the correct use of biosafety measures. Thus observing a decrease in employees due to the low level of sales. This has led to increased unemployment and the risk of business closures. In turn, the reduction in economic income has generated low purchasing power in the community, generating a lack of environmental practices and the spread of diseases. To address these problems, continuous improvement strategies are proposed, these include the implementation of detection technologies, such as thermal cameras and motion sensors, the training and development of workers' skills on health and safety issues, the promotion of remote work and labor flexibility, the application of advanced disinfection technologies, such as ultraviolet light disinfection, the implementation of telemedicine programs and the creation of a digital commercial space. These strategies seek to improve the development of the people who work in the San Cayetano Commercial Passage, reducing the risk of contagion of COVID-19, promoting resilience and adaptability in crisis situations, and contributing to the protection of the environment.